A pathogenic DMC1 frameshift mutation causes nonobstructive azoospermia but not primary ovarian insufficiency in humans. (13th September 2021) - Cao, Dandan; Shi, Fu; Guo, Chenxi; Liu, Ye; Lin, Zexiong; Zhang, Juanhui; Li, Raymond Hang Wun; Yao, Yuanqing; Liu, Kui; Ng, Ernest Hung Yu; Yeung, William Shu Biu; Wang, Tianren
Abstract: Nonobstructive azoospermia (NOA) and diminished ovarian reserve (DOR) are two disorders that can lead to infertility in males and females. Genetic factors have been identified to contribute to NOA and DOR. However, the same genetic factor that can cause both NOA and DOR remains largely unknown. To explore the candidate pathogenic gene that causes both NOA and DOR, we conducted whole-exome sequencing (WES) in a non-consanguineous family with two daughters with DOR and a son with NOA. We detected one pathogenic frameshift variant (NM_007068:c.28delG, p. Glu10Asnfs*31) following a recessive inheritance mode in a meiosis gene DMC1 (DNA meiotic recombinase 1). Clinical analysis showed reduced antral follicle number in both daughters with DOR, but metaphase II oocytes could be retrieved from one of them. For the son with NOA, no spermatozoa were found after microsurgical testicular sperm extraction. A further homozygous Dmc1 knockout mice study demonstrated total failure of follicle development and spermatogenesis. These results revealed a discrepancy of DMC1 action between mice and humans. In humans, DMC1 is required for spermatogenesis but is dispensable for oogenesis, although the loss of function of this gene may lead to DOR. To our knowledge, this is the first report on the homozygous frameshift mutation as causative for both NOA and DOR and demonstrating that DMC1 is dispensable in human oogenesis.